LATEST TRENDS IN TRAINING MARTIAL ARTS ATHLETES: A STUDY OF THE CONTENTS OF ARTICLES PUBLISHED IN THE JOURNAL «TEORIYA I PRAKTIKA FIZICHESKOY KULTURY» - Maltsev G.S. ,; Zekrin F.H. ,; Zebzeev V.V. ,; Gulyaev A.Yu. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify current trends in the training of martial artists based on the content analysis of publications in the journal TiPFK. Methods and structure of the study. The study included a content analysis of sixty issues of the journal "Teoriya i praktika fizicheskoу kultury". (TiPFK) for the period from 2020 to 2024. Two hundred and fifty-seven articles on martial arts were identified. The selected materials were used to study the quantitative and qualitative indicators of the authors' publication activities in various fields and sports disciplines. The goal was to analyze the authors' activity in different sports. Results and conclusions. Current trends in the field of training martial artists are manifested in the emphasis on the physiological aspects of sports (37 works), monitoring the level of athletes' readiness (33), practicing technical and tactical skills (28), studying the history and evolution of sports disciplines (24), psychological training (23) and general physical training (21). However, the study revealed a deficit of publications devoted to the use of information technology in sports (only 4 articles), which contrasts with the importance of this area in the current realities. In total, 15 areas of publication activity of authors in the field of martial arts were identified with a range from 4 to 37 articles, which is clearly visualized in the presented diagram.